Program Guru Penggerak sebagai Agen Transformasi Manajemen Pendidikan: Studi Persepsi Guru: Program Guru Penggerak sebagai Agen Transformasi Manajemen Pendidikan: Studi Persepsi Guru - Nurhuda, Nurhuda; suripah, suripah; Retnawati, Heri; Fitriani, Fitriani (UIR Press, 2026)
The Guru Penggerak Program (PGP) represents a strategic initiative by the Ministry of Education, Culture, Research, and Technology designed to empower teachers as agents of change and to promote transformation and innovation in school-based educational management. This study aims to examine teachers’ perceptions of the PGP, identify barriers encountered during its implementation, and explore the program’s contributions to enhancing teacher professionalism and school governance. Employing a qualitative descriptive design, data were collected through Focus Group Discussions (FGD), interviews, observations, documentation, and a perception questionnaire. The participants consisted of 64 junior high school teachers in Pekanbaru City. The findings reveal that 43.3% of respondents strongly agreed and 42% agreed that the PGP supports educational management transformation and innovation. The program is perceived as strengthening leadership competencies, professional growth, collaborative culture, and learning quality. Despite these positive outcomes, challenges persist, particularly related to limited program follow-up and insufficient structural support.